In Vitro Degradation Rate of Gelatin/Hydroxyapatite CompositeScaffolds Derived from Blue Swimming Crab Shells - Candra Aditya Putra; Widi Widayat (Journal of Creativity Student, 2026)
Bone tissue damage is a serious health problem that requires bone graft treatments. Blue swimming crab shell waste has proven effective for utilization as a hydroxyapatite (HA) source due to its high calcium content. However, HA possesses a drawback in the form of brittle mechanical properties, making the addition of an organic polymer matrix such as gelatin necessary. This study aims to analyze the effect of varying gelatin and HA compositions (6:94, 7:93, and 8:92 wt%) on thein vitro degradation rate of HA-Gel scaffolds. HA was calcined and synthesized using a microwave-assisted precipitationmethod, and subsequently characterized using X-Ray Diffraction (XRD). The scaffolds were fabricated using the slurrycasting method and then dried using the oven drying method. The in vitro degradation rate testing was conducted in a Phosphate Buffered Saline (PBS) solution at a temperature of 37°C for 1, 2, 3, 6, 12, 18, and 24 hours. The XRD resultsvalidated that blue swimming crab shells are effective in producing HA with a phase purity level reaching 99.1%. The fabrication of HA-Gel scaffolds using the slurry casting method successfully formed uniformly shaped scaffolds, althoughsurface defects in the form of voids were present. The in vitro degradation rate exhibited a residual mass of 100–101.8% across all variants, indicating that degradation had not yet occurred; instead, swelling by the gelatin matrix took place. The variant with the highest HA content (94%) demonstrated the largest and most fluctuating mass increase, while the variantwith the highest gelatin content (8%) was the most stable, indicating good mass resistance of the HA-Gel scaffolds duringthe initial immersion phase.